TikTok Battlefield: Comparative Analysis of English and Arabic Language Representations of The 2022 Russian Ukrainian Conflict On TikTok - ElHawary, Dina Magdeldin Mahmoud (AUC Knowledge Fountain, 2023)
This study extends the growing political communication research on TikTok platform through studying the representation of a major political conflict in modern history; the 2022 Russian Ukrainian conflict. The study is providing a cross cultural comparison by studying the perspectives of English and Arabic speakers about the conflict. The study is based on the analysis of the 500 most liked TikTok videos - in one month duration that starts with the day of the Russian invasion - with top hashtags about the conflict in order to find the common message themes. The study uses a multi-dimensional analysis approach of connective action, collective action, and issue-specific frames to understand how TikTok was used as a social mobilization tool in reference to the conflict and how the users' languages affected these frames. The study also looked at the use of technology affordances to create memetic dimensions of content, form, and stance. As each political conflict represents its own circumstances and dynamics, unlike TikTok’s nature, this study found that the artistic / humorous message theme did not represent the most prominent theme in both Arabic and English language videos. Also, message themes of victims and activists’ reference were more prevalent in English language videos in comparison to Arabic language videos. The results also revealed that connective action frames (personal experiences and emotional commentary) and collective action frames (perceived injustice and agency) were widely utilized in English language videos. However, issue-specific frames (problem definition) were widely found in Arabic language videos. Additionally, the most prominent tone of communication was found to be “serious” in both English and Arabic language videos, and the most prominent communicative function was “referential communication”. The most important finding of this study was the change in TikTok usual usage of playful communication in favor of serious and informative content. Moreover, TikTok unique affordances of association “Duets and stitches” were rarely used in the examined videos. The practical implication of this study is to understand TikTok’s position on the map of social media political expression, given the application’s unique affordances. The present research coming from the MENA region and comparing it with the other world aims at crossing the gap in comparative research by examining how the playful platform is used among English and Arabic speakers posting about a political conflict of a global impact.